Measurement of the subarachnoid space by ultrasound in preterm infants. Issue 2 (1st March 2002) - Armstrong, D L; Bagnall, C; Harding, J E; Teele, R L
Abstract : Background: Measurements of the subarachnoid space during routine cranial sonography may provide an indirect method of monitoring brain growth in preterm infants. Methods: The width of the subarachnoid space was measured on coronal views during head sonography. Initial scans (within five days of birth) were compared with follow up scans. Results: A total of 361 scans were performed on 201 preterm infants. The mean width of the subarachnoid space was < 3.5 mm for 95% of initial scans. It was slightly larger in neonates born closer to term, the equivalent of an increase of 0.02 mm/gestational week (95% confidence interval 0 to 0.10 mm) for initial scans. When the scans of all infants, born at 24–36 gestational weeks who were 36 weeks corrected gestational age were compared, the mean (SD) subarachnoid space was 60% larger for follow up scans than for intial scans: 3.2 (1.38) v 1.95 (1.35) mm (p = 0.002) or the equivalent of a mean increase of 0.20 mm/week (95% confidence interval 0.15 to 0.30 mm) for follow up scans. At 36 weeks corrected gestational age, mean head circumference was not different between those having initial or follow up scans (33.0 (2.0) v 32.2 (1.9) cm; p = 0.31). Conclusions: The mean subarachnoid space is normally < 3.5 mm in preterm infants. The difference between initial and follow up scans suggests reduced brain growth in extrauterine preterm babies.